Review of studies of superradiative microwave generation in X band and Ka band relativistic BWOs; IEEE Transactions on Plasma Science; Vol. 32, iss. 3, pt. 1 - El'chaninov A. A. Anton Aleksandrovich; Korovin S. D. Sergei Dmitrievich; Mesyats G. A. Gennady Andreyevich; Pegel I. V. Igor Valerievich; Rostov V. V. Vladislav Vladimirovich; Shpak V. G.; Yalandin М. I. Michael Ivanovich (2004, 2004)
Title screen